Spectral Domain Optical Coherence Tomography in a Murine Retinal Detachment Model - Cebulla, Colleen M. (2010)
Spectral domain optical coherence tomography (SD-OCT) was used to image retinal detachments in vivo, in a murine model of retinal detachment. Subretinal injections of hyaluronic acid (Healon) were delivered to the right eye of seventeen 10–20 week-old C57Bl6 mice. Evaluation of the fundus with an operating microscope and fundus photography were performed. In vivo, non-contact, ultra high resolution SD-OCT imaging was performed on day 0, day 1–2, day 5–6 and day 15–16. The retinal morphology at the edge and in the area of maximal RD was evaluated. Eyes were enucleated for histologic analysis. The retinal detachment was confirmed by microscopy in all mice. The extent of the retinal detachment was evaluated by measuring the height of the retinal detachment. The retinal layers, including the photoreceptor layer, were evaluated. Retinal layers appeared indistinct soon after RD (day 1, 5), particularly over areas of maximal detachment. By day 5 and 15 the external limiting membrane was no longer visible and there was increased reflectivity of the photoreceptor layer and undulation of the outer retina in areas of RD on both SD-OCT and histology. The thickness of the outer nuclear layer and photoreceptor outer segments decreased on day 5 and 15. SD-OCT is a promising technology to follow retinal detachment and outer retinal abnormalities in a murine model.